Cancer stem cells: a model in the making - Marotta, Lauren L Campbell; Polyak, Kornelia (Current opinion in genetics & development, 2009)
Cancer stem cells and their potential roles in tumor heterogeneity are currently subjects of intense investigation. Studies suggest that these cells may develop from any normal cell and have begun to elucidate their molecular profiles. The percentage of a tumor composed of cancer stem cells varies greatly, and researchers believe that multiple types of these cells may exist in a single neoplasm. Cancer stem cells may be formed by epithelial–mesenchymal transition and seem to be less prevalent in metastases than in corresponding primary tumors. These cells appear to have therapeutic sensitivities different from those of cancer cells with more differentiated features. Looking into the many questions that remain about the cancer stem cells model might lead to more effective cancer prevention, diagnosis, and treatment.